2011
DOI: 10.3233/bd-2010-0323
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, BRCA2 expression, and the androgen receptor CAG repeat region in Egyptian and Moroccan male breast cancer patients

Abstract: Introduction Male breast cancer (MBC) is a rare disease. Rates of MBC in Northern Africa vary by region. The age-standardized incidence for MBC is higher in Morocco than in Egypt, and the Egyptian rate is similar to the U.S of approximately 1/105 . This study aimed at investigating the clinical and molecular characteristics of MBC in Egypt and Morocco. Methods This case-case study included 211 cases from Egypt and 132 from Morocco. Tumor tissues were available for 47 Egyptian and 18 Moroccan patients. Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Family history is relevant for both sexes 7,8 , and BRCA2 mutations and rearrangements play a particularly prominent role in male breast cancer. 9,10,11 Conditions that alter the ratio of estrogen to androgen have been linked to breast cancer risk in men. Klinefelter's syndrome, exogenous estrogen or testosterone use, obesity and a history of prostate cancer treated with estrogens have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Family history is relevant for both sexes 7,8 , and BRCA2 mutations and rearrangements play a particularly prominent role in male breast cancer. 9,10,11 Conditions that alter the ratio of estrogen to androgen have been linked to breast cancer risk in men. Klinefelter's syndrome, exogenous estrogen or testosterone use, obesity and a history of prostate cancer treated with estrogens have been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a comparative study of Male BC between Egypt and Morocco [20], Gilbert et al found that Egyptian men have a younger mean age at diagnosis of 57.5 years, whereas the mean age at diagnosis of Moroccan men was 63.9 years (p=0.0002). Another highlight lays in the underlying liver damages that were noticed in 28 % of Egyptian patients vs only 0.8 % in the Moroccan patients (p<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Common clinical presentations of male breast cancer include painless subareolar lump and nipple discharge 6. Advanced age, family history of breast cancer and BRCA2 contribute to increased risk of developing breast cancer in man 7 8. Exogenous oestrogen usage, obesity, orchitis and Klinefelter’s syndrome, all of which contribute to a higher ratio of oestrogen to testosterone, resulted in elevated male breast cancer risk 5…”
Section: Discussionmentioning
confidence: 99%